Abscisic-acid-responsive StlncRNA13558 induces StPRL expression to increase potato resistance to Phytophthora infestans infection - Shang, Kaijie; Wang, Ruolin; Cao, Weilin; Wang, Xipan; Wang, Yubo; Shi, Zhenting; Liu, Hongmei; Zhou, Shumei; Zhu, Xiaoping; Zhu, Changxiang (Frontiers in Plant Science, 2024)
Late blight, caused by Phytophthora infestans, is one of the most serious diseases affecting potatoes (Solanum tuberosum L.). Long non-coding RNAs (lncRNAs) are transcripts with a length of more than 200 nucleotides that have no protein-coding potential. Few studies have been conducted on lncRNAs related to plant immune regulation in plants, and the molecular mechanisms involved in this regulation require further investigation. We identified and screened an lncRNA that specifically responds to P. infestans infection, namely, StlncRNA13558. P. infestans infection activates the abscisic acid (ABA) pathway, and ABA induces StlncRNA13558 to enhance potato resistance to P. infestans. StlncRNA13558 positively regulates the expression of its coexpressed PR-related gene StPRL. StPRL promotes the accumulation of reactive oxygen species and transmits a resistance response by affecting the salicylic acid hormone pathway, thereby enhancing potato resistance to P. infestans. In summary, we identified the potato late blight resistance lncRNA StlncRNA13558 and revealed its upstream and downstream regulatory relationship of StlncRNA13558. These results improve our understanding of plant-pathogen interactions' immune mechanism and elucidate the response mechanism of lncRNA-target genes regulating potato resistance to P. infestans infection.